STRATEGI GURU PAI DALAM PENGUATAN AKIDAH PESERTA DIDIK SMA NEGERI 1 RAJA AMPAT - Ajirah; Rasyid, Muhammad Rusdi; Sudirman (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2023)
The objectives of this scientific research are: First; describe the strategic process of Islamic religious education teachers in strengthening the faith of Raja Ampat State High School 1 students. Second; analyzing the forms of Islamic religious education teachers' strategies in strengthening the faith of Raja Ampat 1 State High School students.This type of research is Qualitative Description. The research approach is an Islamic educational, normative theological and sociological approach. Research data sources are primary data sources and secondary data sources. Research data collection methods use observation, interviews and documentation methods. Data processing and analysis techniques using data reduction, data presentation, comparative analysis of data and drawing conclusions.The results of the research show that: First, the strategic process of Islamic religious education teachers in strengthening the faith of Raja Ampat State High School 1 students is to instill a sense of love for Allah and strengthen the faith through religious programs such as: routine recitations, congregational midday prayers, day celebrations. Islamic holidays and the Khatam Al-Quran (Gaharu) movement program. Second, the forms of strategy for Islamic religious education teachers in strengthening the faith are exemplary strategies, mentoring or supervision strategies and habituation strategies.